Fiber Lasers and Glass Photonics: Materials Through Applications 2018
DOI: 10.1117/12.2314702
|View full text |Cite
|
Sign up to set email alerts
|

Integrated photonic devices with silicon oxycarbide

Abstract: In this paper, we report on the potential of silicon oxycarbide (SiOC) for integrated photonic applications. SiOC films are developed by reactive radio frequency magnetron sputtering from a silicon carbide (SiC) target in the presence of argon and oxygen gases. The optical properties of the developed SiOC film are characterized with spectroscopic ellispometry over a broad wavelength range 300-1600 nm. The refractive index n of the SiOC film is 2.2 at wavelength λ = 1550 nm and the extinction coefficient k is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Silicon oxycarbide (SiOC) is a novel class of glass compounds that has gained momentum in the scientific community and adopted in technologically important applications such as interlayer dielectrics, anode material in lithium-ion batteries, and photoluminescence. Recently, we have introduced SiOC as a potential platform in integrated photonics. , The refractive index of SiOC can be tailored from n = 1.45, corresponding to SiO 2 , to about 3.2, for amorphous SiC. SiOC has the advantage of a low absorption coefficient in the near-infrared region, and low-loss waveguides on silica realized by sputtering have been demonstrated for the first time with a core index of 1.578 and 2.2. , Waveguide attenuation of 2 to 4 dB/cm in the telecom window of 1550 nm has been measured. In comparison with SiON, exhibiting a pronounced absorption peak around 1505 nm due to N–H bonds, SiOC absorption is spectrally flat across the full (S, C, L) telecom bands, offering a tremendous advantage for broadband applications.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Silicon oxycarbide (SiOC) is a novel class of glass compounds that has gained momentum in the scientific community and adopted in technologically important applications such as interlayer dielectrics, anode material in lithium-ion batteries, and photoluminescence. Recently, we have introduced SiOC as a potential platform in integrated photonics. , The refractive index of SiOC can be tailored from n = 1.45, corresponding to SiO 2 , to about 3.2, for amorphous SiC. SiOC has the advantage of a low absorption coefficient in the near-infrared region, and low-loss waveguides on silica realized by sputtering have been demonstrated for the first time with a core index of 1.578 and 2.2. , Waveguide attenuation of 2 to 4 dB/cm in the telecom window of 1550 nm has been measured. In comparison with SiON, exhibiting a pronounced absorption peak around 1505 nm due to N–H bonds, SiOC absorption is spectrally flat across the full (S, C, L) telecom bands, offering a tremendous advantage for broadband applications.…”
mentioning
confidence: 99%
“…The SiOC film was deposited on a silicon wafer with a 6 μm thick silica substrate by using reactive radio frequency (RF) magnetron sputtering from a SiC target in an oxygen and argon atmosphere. Details on the SiOC sputtering procedure can be found in previous publications. , X-ray photoelectron spectroscopy (XPS) measurements revealed that the deposited material contains 45% silicon, 28% oxygen, and 27% carbon, so that the actual chemical composition is Si 0.45 O 0.27 C 0.27 (for brevity, in the remaining of the paper it will be simply referred to as SiOC omitting the subscripts). Good adhesion of the SiOC film on the silica substrate was observed, with no evidence of either pin holes or porosity.…”
mentioning
confidence: 99%
See 3 more Smart Citations